Translation, Cultural Adaptation, Reliability, and Validity Testing of a Chinese Version of the Self-Administered Mediterranean Diet Scale - Li, Jiajia; Ding, Huirong; Wang, Zheng; El-Ansary, Doa; Adams, Roger; Han, Jia; Meng, Shu (Frontiers in Nutrition, 2022)
Mediterranean Diet management for people with Cardiovascular disease (CVD) or CVD risk is supported by evidence, however there is no valid Chinese language instrument for measurement of adherence to this diet. The objective of this study was to generate a Chinese version of the Mediterranean Diet Scale (MDS-Chinese) and to validate a self-administered version with Chinese participants with CVD, or CVD risk. The MDS-Chinese was created by translation and cultural adaptation and tested for psychometric properties. A panel of 10 experts in the field who evaluated the MDS-Chinese content showed that the content validity index ranged from 0.88 to 1.00. Sixteen native Chinese speakers with CVD or CVD risk evaluated the clarity of the MDS-Chinese, and the resulting instruction and items clarity scores ranged from 9.2-10.0. Three hundred and twenty-six participants completed the MDS- Chinese and a Chinese version of the Coronary Artery Disease Education questionnaire short version (CADE-Q SV). Analysis indicated that the MDS-Chinese has 4 factors, and the Pearson’s correlation between the MDS-Chinese and CADE-Q SV was 0.73. Fifty randomly selected participants completed the MDS-Chinese again with a 1-week interval to assess reliability. Internal consistency was acceptable (Cronbach’s α was 0.62) and the inter-class correlation reliability coefficients (ICC) for each item ranged from 0.73-0.88. This study showed that the MDS-Chinese has acceptable reliability and validity for use among those in the Chinese population with CVD or CVD risk. Given that diet is one of key secondary prevention strategies for management in cardiac rehabilitation, the MDS-Chinese instrument may be a useful and convenient tool for use with those in the Chinese population with CVD or with high risk of CVD, to monitor level of MD adherence, information which is important for clinical practice. In addition, the establishment of the MDS-Chinese gives a fundamental tool for diet-related CVD research in the Chinese population. Moreover, employment of the MDS-Chinese in the Chinese community may improve awareness of the importance of a healthy diet in CVD prevention and management.